Effect of the osteotome technique in cases of deficient edentulous ridge - Rammelsberg, Peter; Gabbert, Olaf; Schmitter, Marc; Koob, Andreas; Pritsch, Maria; Faggion Junior, Clóvis Mariano (Journal of oral and maxillofacial surgery, 2011)
Purpose - The use of dental implants may be limited by lack of sufficient bone. The effectiveness of the alveolar ridge bone-spreading technique in the maxilla was compared with the standard technique. Bone spreading is a technique in which hand osteotomes are used to progressively enlarge the remaining deficient edentulous ridge to enable placement of dental implants. - Materials and Methods - In the test group (bone spreading), 72 patients received 126 implants. Thirty-six patients with 63 implants placed with conventional implant preparation served as a control group. Measurements of outcome were implant failure and complications after therapy. Kaplan-Meier curves were used to depict time from implant placement to implant failure or complication. - Results - Six complications were observed after placement of the implants (3 implant failures, peri-implant inflammation in 2 implants, and 1 exposure of rough implant surface). There was a trend toward more implant failures in the control group. - Conclusions - Results of the ridge-spreading technique seem to be similar to those of the standard technique. However, these results should be regarded with caution because of the small number of complications.